Assessment of bed joints behavior of calcium silicate brick masonry during execution. Issue 4 (1st October 2016) - Šlivinskas, Tomas; Jonaitis, Bronius; Drobiec, Łukasz
Abstract: This article examines masonry as the composite material. Factors affecting the mechanical deformation characteristics of masonry bed joints are reviewed. The strength and deformation characteristics of bed joints under the influence of changing mortar strength and variable compressive load are analysed Compressive strength, shrinkage and plastic deformation of masonry fragments and bed joints under variable compressive strength are also examined.